ASSOCIATION OF NKT- AND ACTIVATED CD25+ PERIPHERAL BLOOD LYMPHOCYTES WITH DISEASE FREE AND OVERALL SURVIVAL OF TRIPLE NEGATIVE BREAST CANCER PATIENTS - A. I. Chertkova; E. G. Slavina; T. N. Zabotina; Z. G. Kadagidze; E. K. Shoua; O. O. Gordeeva; I. V. Kolyadina; L. G. Zhukova; I. P. Gan’shina; A. A. Meshcheryakov (Сибирский онкологический журнал, 2020)
Background. We previously found that a decrease in the number of NKT cells and activated CD 25+ peripheral blood lymphocytes (PBLs) before neoadjuvant chemotherapy was associated with an increased likelihood of disease progression in patients with locally advanced triple-negative breast cancer (TN BC).The purpose of this study was to determine the relationship between the initial number of NKT-and CD 25+ PBLs and relapsefree survival (RFS)/overall survival (OS ) in patients with TN BC who received neoadjuvant chemotherapy with cisplatin and paclitaxel followed by surgery.Material and Methods. The study included patients with stage II and III TN BC. The follow-up time was 36 and 66.9 months. Immediately before chemotherapy, the percentage of CD 3+CD 16+CD 56+ (NKT) -, CD 25+- and CD 8+ PBLs was determined by flow cytometry. Statistical analysis of the data was carried out using the Statistics 7 software package. The Kaplan-Meier method was used to determine the relationship between immunological parameters and RFS/ OS .Results. The decreased level of NKT cells before treatment was associated with a decrease in the 3-year RFS [Me: 20.1 (0.533 and 39.7) months] compared to that observed in patients with higher percentage of these cells than in the control (Me was not achieved). There were no statistically significant differences in the 3-year OS between the groups. The initially reduced number of CD 25+ lymphocytes in comparison with the control was associated with decreased rates of both RFS and OS . The difference in DFS and OS was more significant between the groups of patients who simultaneously had an increased initial number of both NKT and CD 25+ cells and patients in whom both cell populations were below normal levels.Conclusion. The initial (prior to chemotherapy) number of NKT and activated CD 25+ PBLs can apparently be a predictive factor in TN BC patients, who received neoadjuvant chemotherapy with cisplatin and paclitaxel.